ADAMTS13-binding IgG are present in patients with thrombotic thrombocytopenic purpura - Tsai, Han-Mou; Raoufi, Mojgan; Zhou, Wenhua; Guinto, Enriqueta; Grafos, Nickolas; Ranzurmal, Safi; Greenfield, Robert S.; Rand, Jacob H. (Thrombosis and Haemostasis, 2006)
Functional assays are commonly used to measure the antibodies of ADAMTS13 found in patients of thrombotic thrombocytopenic purpura (TTP). In this study we used an enzyme-linked immunoassay to analyze the ADAMTS13-binding IgG levels in six groups of individuals: normal, random hospitalized patients, acute TTP,TTP after receiving plasma therapy,TTP in remission, and other types of thrombotic microangiopathy (TMA).The results showed that ADAMTS13-binding IgG levels were elevated in 100% of the acute TTP group, 75% of the TTP group after receiving plasma therapy, and 40% of the remission group. Overall, the ADAMTS13-binding IgG levels correlated with the inhibitory activity levels againstADAMTS13 (r = -0.69,P<0.0001).The assay also detected elevated IgG binding levels in 5% - 15% of the normal, random, and other TMA control groups.Addition of purified ADAMTS13 protein to the plasma samples suppressed the IgG binding in each of the acute TTP patients, but in none of the non-TTP groups. Serial measurement in a patient that had two exacerbations of TTP within the first three weeks revealed that the ADAMTS13 activity levels remained < 0.1 U/ml during this period, and the ADAMTS13-binding IgG remained elevated, suggesting that ADAMTS13 analysis may provide valuable insight to the disease status during the course of therapy. Analysis of ADAMTS13-binding IgG is helpful for the diagnosis and management of TTP.
Keywords: ADAMTS13; thrombotic thrombocytopenic purpura; antibody